E-Learning in the Vortex of the Digital Revolution: An In-Depth Study of Applications and Prospects in Higher Education - Fauzia Salsabillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article presents a comprehensive analysis of the dynamics of e-learning in the context of higher education and its relevance to the Independent Learning Campus (MBKM) policy. The method used is a qualitative and descriptive-analytical literature review, which focuses on synthesizing data from scientific journals and academic publications. The research results identified four main pillars: (1) E-Learning development has evolved from passive CBT to an Adaptive, Mobile and Immersive model supported by AI; (2) There are significant differences in implementation, where universities emphasize autonomy, specialization, and research, in contrast to the instructional nature of schools; (3) The advantages of E-Learning lie in flexibility, cost efficiency, and increasing digital competence, while the disadvantages include infrastructure access challenges and social interaction deficits; and (4) As a contribution to Wiralodra University, it recommends a blended-flexible strategy, increasing lecturer E-Tutor competency, and diversifying digital assessments to overcome access gaps and improve learning quality. In conclusion, E-Learning is a transformative catalyst that requires inclusive pedagogy and careful risk management to optimize its full potential in producing competitive graduates in the digital era.